Tactical strength the elite training and workout plan to build a solid foundation of strength & power - Smith, Stewart 1969- (Hatherleigh Press, 2017)
Tactical Strength presents a series of workout plans designed for both men and women--programs based in weight lifting, body weight calisthenics, cardiovascular training, and swimming-- scaled for a variety of levels.